2012
DOI: 10.1245/s10434-012-2460-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychological Impact of BRCA Genetic Counseling in Before and After Definitive Surgery Breast Cancer Patients

Abstract: Purpose This study examined changes in cancer-related knowledge, distress, and decisional conflict from pretest- to post-genetic counseling (GC) in before definitive surgery (BDS) and after definitive surgery (ADS) breast cancer (BC) patients. Methods Sociodemographic and clinical characteristics were collected at baseline; primary outcome data were collected before (T1) and after (T2) pretest GC. Within group changes for cancer-related knowledge, distress, and decisional conflict over GT were compared using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…21,22 By contrast, qualitative data indicate that women with breast cancer have a positive attitude toward RGCT, 23 and results of a pilot study have suggested that genetic counseling before definitive surgery does not increase distress levels. 24 The results of our trial provide additional evidence in this regard. However, we emphasize the need to confirm our results in future studies.…”
Section: Discussionmentioning
confidence: 58%
“…21,22 By contrast, qualitative data indicate that women with breast cancer have a positive attitude toward RGCT, 23 and results of a pilot study have suggested that genetic counseling before definitive surgery does not increase distress levels. 24 The results of our trial provide additional evidence in this regard. However, we emphasize the need to confirm our results in future studies.…”
Section: Discussionmentioning
confidence: 58%
“…13,26 Better outcomes when genetic counseling is performed by a GC compared with nongenetics physicians are not unexpected, given that nongenetics physicians often self-report little or no genetics training and low competence in genetics. [27][28][29] Compounding factors include increasing demands on physician time, shorter encounters with patients, and limited mechanisms for clinician training in genetics.…”
Section: Use and Outcomes Of Brca Testing And Counseling In Insured Wmentioning
confidence: 99%
“…Furthermore, results from this sample reported in an earlier manuscript found no changes in cancer distress or decisional conflict about genetic testing following the pre-test genetic counseling session [26]. However, it is unclear what aspects of genetic counseling caused these positive changes.…”
Section: Discussionmentioning
confidence: 71%
“…The methods used for the study are reported in greater detail in previous reports [26,27] and are briefly summarized below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation